2017
DOI: 10.1007/s10517-017-3606-4
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Release-Active Antibodies to CD4 Receptor on the Level of lck-Kinase in Cultured Mononuclear Cells from Human Peripheral Blood

Abstract: For evaluation of effects of release-active antibodies to CD4 on cultured lymphocytes from human peripheral blood, we measured intracellular content of lck-kinase cell-based ELISA. In cells treated with release-active antibodies to CD4, the content of intracellular lck-kinase significantly (p<0.01) decreased in comparison with the control (purified water processed in a similar way). Phytohemagglutinin had no effect on the concentration of lck-kinase in cells. The decrease in the content of CD4-associated lck p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
4
0
1
Order By: Relevance
“…This assumption is consistent with the data previously obtained in vitro. It has been shown that TPA to CD4 affect activity of Lck-kinase [16] associated with the cytoplasmic part of the CD4 + and CD8 + co-receptors on T helpers and T killers, respectively, and is involved in the signal transduction from the T-cell receptor. In addition, administration of TPA to CD4 receptor to Jurkat cells increased secretion of IL-2, the main participant of T-cells differentiation and proliferation [9].…”
Section: Resultsmentioning
confidence: 99%
“…This assumption is consistent with the data previously obtained in vitro. It has been shown that TPA to CD4 affect activity of Lck-kinase [16] associated with the cytoplasmic part of the CD4 + and CD8 + co-receptors on T helpers and T killers, respectively, and is involved in the signal transduction from the T-cell receptor. In addition, administration of TPA to CD4 receptor to Jurkat cells increased secretion of IL-2, the main participant of T-cells differentiation and proliferation [9].…”
Section: Resultsmentioning
confidence: 99%
“…It also improves the ligand-receptor interaction of IFN-g with its receptor, normalizes the concentration and functional activity of natural antibodies to IFN-g, induces antigen expression of major histocompatibility complex (MHCI and MHCII) and Fc-receptors, stimulates natural killer (NK) cell and monocyte functional activity, and activates a mixed Th1 and Th2 immune response. 16,25 Other components of the drug, technologically treated forms of antibodies to histamine and to CD4, have effects on histamine receptor 26 and CD4 receptor, 27 respectively. This study has some limitations that could be considered as sources of bias: the open-label trial design, the absence of a placebo group and an untreated group, the long enrollment period (such that the outcome of many patients was known before others had been enrolled), a number of measurements of key variables performed, and the use of patient self-report.…”
Section: Discussionmentioning
confidence: 99%
“…ТО антитела к ИФН-γ проявляют иммуномодулирующую активность, что выражается в увеличении продукции ИФН-γ лимфоцитами и сопряженных с ИФН-γ цитокинов (интерлейкина-2, интерлейкина-4, интерлейкина-10), регуляции активности Th1 и Th2, активации клеточного и гуморального иммунного ответа, увеличении соотношения CD4+/CD8+ лимфоцитов, повышении функциональной активности естественных киллеров, нейтрофилов и макрофагов*. ТО антитела к CD4 регулируют активность ко-рецептора CD4 Т-клеточного рецептора, усиливая передачу сигнала с Т-клеточного рецептора, что показано in vitro по снижению уровня адаптерной молекулы CD4 лимфоцит-специфической киназы (Lck) в лимфоцитах периферической крови здоровых доноров, которое происходит после успешного взаимодействия CD4 с антигеном в комплексе с МНС II [15]. При этом классической антигенной стимуляции препарат не оказывает.…”
Section: Original Articleunclassified